Klitik Klausa Pasif Bahasa Manggarai Dialek Barat Buha Aritonang - Buha Aritonang (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2018)
Clitics is one of the language systems retained in the Western dialect of Manggarai. The clitics in that language is a bound form that phonologically has no stress and its form can not be regarded as a bound morpheme. To analyze it is used clitics theory. The purpose of this study is to describe the type of clitics, the proclitics form, and its manifestation in the passive clause of Western dialect of Manggarai language. The research method used is descriptive-qualitative method. The results of this study indicate that (1) the type of clitics in the Manggarai language of the Western dialect is classified into a prestigious prestigious proclitics, pronominal genetic encryption, and the pronominal enclosure of the subject; (2) the proximal pronounced pronominal form de= alomorfed with d= and belongs to the prestigious pronominal possessive. The form of de proclitics follows the / h / consonant, whereas d= follows the vowel form; proximal pronominal to the proper noun in the form of di=; the name of pronoun is de =, and the name of office (social status) is de =; and (3) the pronominal and genetic encryption of pronominal subjects can be manifested in the construction of the Western Manggarai dialect's passive clause.—Klitik merupakan salah satu sistem bahasa yang terdapat dalam bahasa Manggarai dialek Barat. Klitik dalam bahasa itu merupakan bentuk terikat yang secara fonologis tidak memiliki tekanan sendiri dan bentuknya tidak dapat dianggap sebagai morfem terikat. Untuk menganalisinya digunakan teori morfologi. Tujuan penelitian ini adalah mendeskripsikan jenis klitik, bentuk proklitik, dan perwujudannya dalam klausa pasif bahasa Manggarai dialek Barat. Metode penelitian yang digunakan adalah metode deskriptif-kualitatif. Hasil penelitian ini menunjukkan bahwa (1) jenis klitik dalam bahasa Manggarai dialek Barat diklasifikasikan menjadi proklitik pronominal posesif, enklitik pronominal genetif, dan enklitik pronominal subjek; (2) bentuk proklitik pronominal posesif de= beralomorf dengan d= dan tergolong sebagai proklitik pronominal posesif. Bentuk proklitik de= mengikuti bentuk berawalan konsonan /h/, sedangkan d= mengikuti bentuk vokal; proklitik pronominal posesif untuk nama diri insan berupa di=; nama diri bukan insan berupa de=, dan nama jabatan (status sosial) berupa de=; dan (3) enklitik pronominal genetif dan enklitik pronominal subjek dapat diwujudkan dalam kontruksi klausa pasif bahasa Manggarai dialek Barat. DOI : 10.15408/bat.v24i1.7191